2004
DOI: 10.1017/s1743921304005307
|View full text |Cite
|
Sign up to set email alerts
|

The Sunspot Activity in the Last Two Millenia on the Basis of Indirect and Instrumental Indexes: Time Series Models and Their Extrapolations for the 21st Century

Abstract: In the present study a time series analysis of three of the most well-known Sun activity data series is made: 1) the Hoyt-Schatten (Group Sunspot Number $\mbox{\textit{Rg}}$)(Hoyt & Schatten 1988); 2) the Schove and 3) the Greenland (Dye-3 ice probe) ‘cosmogenic’ $^{10}Be$ concentration series (Schove 1983, Beer et al. 1998). The series “1” is based on instrumental observations for the last $\sim$400 years. The series “2” is a reconstruction of all Schwabe-Wolf cycle magnitudes after AD 296 by use of historica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In the 1960s, it was shown that the above-mentioned fluctuations are connected to long-term solar activity variations [13] and that they have been cyclic with a mean period of ~200 years during the last ~1300 years [12]. The existence of a bi-century cycle in the cosmogenic isotope 14 C and 10 Be time series, as well as its solar origin during the last ~50 years, was reported by many other authors [14][15][16]26]. The 200 yr oscillation is often also labeled the "Suess cycle" in honor of one of its co-discoverers, the Austrian-American chemist and nuclear physicist Hans Eduard Suess ((1909-1993), https://en.wikipedia.org/wiki/Hans_Suess; accessed on 15 December 2023).…”
Section: The "Nitrate Method"mentioning
confidence: 80%
“…In the 1960s, it was shown that the above-mentioned fluctuations are connected to long-term solar activity variations [13] and that they have been cyclic with a mean period of ~200 years during the last ~1300 years [12]. The existence of a bi-century cycle in the cosmogenic isotope 14 C and 10 Be time series, as well as its solar origin during the last ~50 years, was reported by many other authors [14][15][16]26]. The 200 yr oscillation is often also labeled the "Suess cycle" in honor of one of its co-discoverers, the Austrian-American chemist and nuclear physicist Hans Eduard Suess ((1909-1993), https://en.wikipedia.org/wiki/Hans_Suess; accessed on 15 December 2023).…”
Section: The "Nitrate Method"mentioning
confidence: 80%
“…In the latter work, published his-torical data from the catalog of Křivský and Pejml [1988] was used. There is also a 200-210-year cycle in "cosmogenic" radio isotopes ( 14 C, 10 Be), relating to GCR flux variations [Damon and Sonett, 1991;Dergachev, 1994;Komitov and Kaftan, 2004;Stuiver and Quay, 1980;Suess, 1980]. All these facts support the solar origin of the ∼200-250-year cycle in the volcanic eruption time series during the past ∼470 years.…”
Section: Discussionmentioning
confidence: 92%
“…Climatic events throughout history, such as ice ages and warmer weather periods, correlate with periods of solar activity or with variations in total solar radiation. One of the most significant minima of solar activity was the Dalton minimum, which occurred in the periods 1790-1830 and 1796-1820, depending on the solar cycle they join (Komitov and Kaftan, 2004). In that period, below-average temperatures appeared in Great Britain.…”
Section: Wolf's Number and The Hurst Phenomenonmentioning
confidence: 99%